Meningkatkan Aktivitas dan Hasil Belajar Siswa Melalui Pembelajaran Kooperatif Stad pada Siswa Kelas IX A MTs Negeri 5 Bojonegoro - Rukhaniyah, Rukhaniyah (Jurnal Ilmiah Guru Madrasah, 2023)
To overcome the problem of low learning outcomes and student activity in learning, it is necessary to conduct research on the application of learning that can increase student activity and learning outcomes, one of which is by applying STAD (Student Teams Achievement Divisions) cooperative learning with a contextual approach. Through the application of this learning it is hoped that it can increase the activity and results of Physics learning for class IX students at MTs Negeri 5 Bojonegoro. This research is a class action research carried out in 2 cycles of action, each cycle consisting of one meeting for 2 hours of lessons. The research subjects were 32 students in class IX A in the odd semester of the 2022/2023 academic year at MTs Negeri 5 Bojonegoro. The instruments used were test questions, student and teacher activity observation sheets, and field notes. The results showed that the application of STAD cooperative learning could increase the activity and learning outcomes of Physics students in class IXA MTs Negeri 5 Bojonegoro. The increase in student learning activity was indicated by an increase in the average percentage of student learning activity and the success rate of action in the first cycle of 63.52% (enough) increased to 71.34% (good) in the second cycle. The increase in student learning outcomes can be seen from the average difference in score between the pre-test and post-test of 32.92 in cycle I and increased again to 34.65 in cycle II, while student learning completeness in cycle I increased by 77.78% to 86.11% in cycle II Abstrak Untuk mengatasi permasalahan rendahnya hasil belajar dan aktivitas siswa dalam pembelajaran, maka perlu dilakukan penelitian tentang penerapan pembelajaran yang dapat meningkatkan aktivitas dan hasil belajar siswa, salah satunya dengan penerapan pembelajaran kooperatif  STAD (Student Teams Achievement Divisions) dengan pendekatan kontekstual. Melalui penerapan pembelajaran tersebut diharapkan dapat meningkatkan aktivitas dan hasil belajar Fisika siswa kelas IX di MTs Negeri 5 Bojonegoro.Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam 2 siklus tindakan, setiap siklus terdiri atas satu kali pertemuan selama 2 jam pelajaran. Subjek penelitian adalah siswa kelas IX A semester gasal tahun ajaran 2022/2023 MTs Negeri 5 Bojonegoro yang berjumlah 32 siswa. Instrumen yang digunakan soal tes, lembar observasi aktivitas siswa dan guru, dan catatan lapangan.Hasil penelitian menunjukkan  bahwa penerapan pembelajaran kooperatif STAD dapat meningkatkan aktivitas dan hasil belajar Fisika siswa kelas IXA MTs Negeri 5 Bojonegoro. Peningkatan aktivitas belajar siswa ditunjukkan dengan peningkatan rata-rata persentase aktivitas belajar siswa dan taraf keberhasilan tindakan pada siklus I 63,52% (cukup) meningkat menjadi 71,34% (baik) pada siklus II. Peningkatan hasil belajar siswa dapat diketahui dari rata-rata selisih skor antara pre-test dan post test sebesar 32,92 pada siklus I dan meningkat lagi menjadi 34,65 pada siklus II, sedangkan ketuntasan belajar siswa pada siklus I sebesar 77,78% meningkat menjadi 86,11% pada siklus II.